2016
DOI: 10.1111/cen.13141
|View full text |Cite
|
Sign up to set email alerts
|

ACTH and gonadotropin deficiencies predict mortality in patients treated for nonfunctioning pituitary adenoma: long‐term follow‐up of 519 patients in two large European centres

Abstract: SummaryContext and ObjectiveNonfunctioning pituitary adenomas (NFPAs) are the most common subtype of pituitary tumour. Hypopituitarism is observed in NFPAs due to tumour‐ or treatment‐related factors and may increase mortality risk. Here, we analysed the associations of hypopituitarism, hormone replacement and mortality in a large NFPA cohort derived from two large European centres.Design, Setting and ParticipantsCase note review of all patients treated for NFPA in University Hospitals Birmingham and Beaumont … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 39 publications
(53 reference statements)
6
41
0
1
Order By: Relevance
“…The debate regarding the long‐term risks of RT in NFPA has been well rehearsed . Two recent well‐designed large retrospective cohort studies have examined the mortality of patients with NFPA . The predictors of mortality were found to be age as well as ACTH and gonadotrophin (Gn) deficiency .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate regarding the long‐term risks of RT in NFPA has been well rehearsed . Two recent well‐designed large retrospective cohort studies have examined the mortality of patients with NFPA . The predictors of mortality were found to be age as well as ACTH and gonadotrophin (Gn) deficiency .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent well‐designed large retrospective cohort studies have examined the mortality of patients with NFPA . The predictors of mortality were found to be age as well as ACTH and gonadotrophin (Gn) deficiency . RT was associated with lower age of death, higher relative risk of death and a trend towards a higher relative risk of cerebrovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…Two large registry-based studies of patients with PAI have shown that despite adequate glucocorticoid replacement, the relative risk of death for these patients is more than double that of the background population. [15][16][17] Two large cohort studies of patients with hypopituitarism (one study comprising of patients with acromegaly and the other patients with nonfunctioning pituitary adenomas) have shown that ACTH deficiency and higher doses of hydrocortisone are associated with increased mortality. 12,14 Patients with SAI also have increased morbidity and mortality.…”
Section: Mortalit Y and Morb Id It Y In Adrenal Insufficien C Ymentioning
confidence: 99%
“…[11][12][13] Leading causes of death are adrenal crisis, infections, cardiovascular disease and malignancy. 16,17 It is possible that even subtle increases in glucocorticoid exposure in patients on replacement therapy over prolonged periods of time may contribute to increased morbidity and mortality, as occurs in patients with Cushing's syndrome. [15][16][17] Two large cohort studies of patients with hypopituitarism (one study comprising of patients with acromegaly and the other patients with nonfunctioning pituitary adenomas) have shown that ACTH deficiency and higher doses of hydrocortisone are associated with increased mortality.…”
Section: Mortalit Y and Morb Id It Y In Adrenal Insufficien C Ymentioning
confidence: 99%
See 1 more Smart Citation